Hermite-Hadamard-type inequalities for generalized trigonometrically and hyperbolic ρ-convex functions in two dimension - Dragomir, Silvestru Sever; Jleli, Mohamed; Samet, Bessem (Open mathematics (Warsaw, Poland), 2024)
In this article, we establish Hermite-Hadamard-type inequalities for the two classes of functions , where and is an open subset of . We also obtain a characterization of the set . Notice that in the one-dimensional case, if (an open interval of ) and , , then (resp. ) reduces to the class of functions such that is trigonometrically -convex (resp. hyperbolic -convex) on